2019
DOI: 10.1016/j.epsr.2019.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Improving DTR assessment by means of PCA applied to wind data

Abstract: Traditionally, the rating of an overhead transmission line is determined under a set of specified and standardized conditions. However, weather conditions along the line change during operation. Therefore, the standard rating of the line might be either underestimated, leading to inefficient utilization of the line, or overestimated, leading to unsecure operation. This is the major drawback of the traditional approach: the so-called Dynamic Thermal Rating (DTR), that takes into account the actual operating con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The forecast data is augmented with real-time weather information from local weather stations placed along the overhead lines (Carlini, 2020). Moreover, principal component analysis (PCA) method is utilized, given the large volume of data provided by real-time measurements and weather forecasts, with a space-time model based on clustering, extrapolation and interpolation techniques (Bosisio et al, 2019).…”
Section: Wide-area Weather-based Indirect Dlr Systemsmentioning
confidence: 99%
“…The forecast data is augmented with real-time weather information from local weather stations placed along the overhead lines (Carlini, 2020). Moreover, principal component analysis (PCA) method is utilized, given the large volume of data provided by real-time measurements and weather forecasts, with a space-time model based on clustering, extrapolation and interpolation techniques (Bosisio et al, 2019).…”
Section: Wide-area Weather-based Indirect Dlr Systemsmentioning
confidence: 99%
“…As such, steady-state ampacity is predicted using wind simulations coupled with meteorological records. Bosisio et al [20] built a step-by-step method for evaluating all of the stochastic processes of atmospheric variables usable for DLR forecasting. Albizu et al [21] suggested an adaptive SLR for static line rating situations that could reach a maximum temperature limit.…”
Section: A Literature Surveymentioning
confidence: 99%
“…e PCA algorithm calculates the eigenvalues of the input variable matrix, finds the variance corresponding to each input variable, and then determines the PC according to the cumulative value [28]. e main steps are as follows.…”
Section: Meteorological Feature Extraction Based On Principalmentioning
confidence: 99%